Cloning and characterization of a cDNA encoding transformation-sensitive tropomyosin isoform 3 from tumorigenic human fibroblasts. - Lin, C S (1988)
We isolated a cDNA clone from the tumorigenic human fibroblast cell line HuT-14 that contains the entire protein coding region of tropomyosin isoform 3 (Tm3) and 781 base pairs of 5'- and 3'-untranslated sequences. Tm3, despite its apparent smaller molecular weight than Tm1 in two-dimensional gels, has the same peptide length as Tm1 (284 amino acids) and shares 83% homology with Tm1. Tm3 cDNA hybridized to an abundant mRNA of 1.3 kilobases in fetal muscle and cardiac muscle, suggesting that Tm3 is related to an alpha fast-tropomyosin. The first 188 amino acids of Tm3 are identical to those of rat or rabbit skeletal muscle alpha-tropomyosin, and the last 71 amino acids differ from those of rat smooth muscle alpha-tropomyosin by only 1 residue. Tm3 therefore appears to be encoded by the same gene that encodes the fast skeletal muscle alpha-tropomyosin and the smooth muscle alpha-tropomyosin via an alternative RNA-splicing mechanism. In contrast to Tm4 and Tm5, Tm3 has a small gene family, with, at best, only one pseudogene.